ANALISIS PENDAPATAN USAHATANI SAYURAN DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Kinanti, Namira; Haryono, Dwi; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purposes of this research are to analyze the income of each type of vegetable farming (chilli, tomato, chicory, cucumber and cabbage), the income based on the various cropping pattern of vegetables, the cropping pattern which gives the highest income. This research was conducted with a survey method in Sumberejo Subdistrict of Tanggamus Regency and the location was selected purposively. Respondents were 53 vegetable farmers taken using Stratified Random Sampling method and determined the allocation of the proportion of the sample according to the cropping pattern. The analytical method used was farm income analysis by Rahim and Hastuti (2008). The results showed that chilli, tomato, chicory, cucumber, and cabbage farming are profitable because of the values of R/C ratio > 1. The income of vegetable farming cropping pattern 1, 2, 3 in a row are Rp203,826,644.43; Rp221,730,908.34 and Rp253,833,536.82 so that the cropping pattern that most profitable for farmers is vegetable farming cropping pattern 3 (chili-tomato-cabbage) with the value of R/C of 3.98. Key words: cropping pattern, income, vegetable farming